Experiments on double diffusive convection - Tilgner, Andreas (Comptes Rendus. Physique)
Double diffusive convection is a form of convection that was studied in the past mostly for its application in oceanography and which receives increasing attention in the context of planetary cores. This review will focus on measurements of transport properties of double diffusive convection which were performed in two types of experiments: the experiments either start from two layers separated by a sharp interface, or they investigate convection within uniform gradients. The most recent experiments were done on the finger regime in which the slowly diffusing component drives the motion while the rapidly diffusing component stabilizes the fluid and this review is restricted to this configuration.